Comparison of protocols measuring diffusion and partition coefficients in the stratum corneum. Issue 7 (31st January 2017) - Rothe, H.; Obringer, C.; Manwaring, J.; Avci, C.; Wargniez, W.; Eilstein, J.; Hewitt, N.; Cubberley, R.; Duplan, H.; Lange, D.; Jacques‐Jamin, C.; Klaric, M.; et al.
Abstract: Partition (K) and diffusion (D) coefficients are important to measure for the modelling of skin penetration of chemicals through the stratum corneum (SC). We compared the feasibility of three protocols for the testing of 50 chemicals in our main studies, using three cosmetics‐relevant model chemicals with a wide range of logP values. Protocol 1: SC concentration‐depth profile using tape‐stripping (measures KSC/v and DSC /HSC 2, where HSC is the SC thickness); Protocol 2A: incubation of isolated SC with chemical (direct measurement of KSC/v only) and Protocol 2B: diffusion through isolated SC mounted on a Franz cell (measures KSC/v and DSC /HSC 2, and is based on Fick's laws). KSC/v values for caffeine and resorcinol using Protocol 1 and 2B were within 30% of each other, values using Protocol 2A were ~two‐fold higher, and all values were within 10‐fold of each other. Only indirect determination of KSC/v by Protocol 2B was different from the direct measurement of KSC/v by Protocol 2A and Protocol 1 for 7‐EC. The variability of KSC/v for all three chemicals using Protocol 2B was higher compared to Protocol 1 and 2A. DSC /HSC 2 values for the three chemicals were of the same order of magnitude using all three protocols. Additionally, using Protocol 1, there was very little difference between parameters measured in pig and human SC. In conclusion, KSC/v, and DSC values were comparable using different methods. Pig skin might be a good surrogate for human skin for the three chemicals tested. Copyright © 2017 The Authors Journal of Applied Toxicology published by John Wiley & Sons Ltd. Abstract : We compared protocols measuring diffusion and partition coefficients of caffeine, resorcinol and 7‐ethoxycoumarin in the stratum corneum: Protocol 1: SC concentration‐depth profile using tape‐stripping; Protocol 2A: incubation of isolated SC with chemical and Protocol 2B: diffusion through isolated SC mounted on a Franz cell, with non‐linear regression fitted data. The different methods produced comparable results and demonstrated that waste pig skin might be a good surrogate for human skin for the three chemicals tested.